Konsep Pembelajaran Mahasiswa Dalam Memahami Algoritma Melalui Komputer Pemograman - Icha Amelia; Yahfizham Yahfizham (Jurnal Teknik Informatika dan Teknologi Informasi, 2023)
A programing algorithm means a number of activities to complate a process. Its done according to the procedure. Algorithm can be basis for the development of computer programs. The core of the science is algorithms.. The literary based on data metodology found in various refrences. The goal is tho get help students recognize and faciliate student understanding theeby increasing motivation in learning.